Structural factors influencing the clinical performance of 0.025-inch guidewires for pancreatobiliary endoscopy: An experimental study - Koga, Takehiko; Tsuchiya, Naoaki; Ishida, Yusuke; Kitaguchi, Takanori; Matsumoto, Keisuke; Fukuyama, Makoto; Kojima, Satoki; Kojima, Norihiro; Hirai, Fumihito (Endoscopy International Open, 2024)
Background and study aims To develop a pancreatobiliary endoscopic guidewire with good clinical performance, an understanding of its structure is necessary. This study aimed to investigate the structural factors influencing the clinical performance of pancreatobiliary endoscopic guidewires.Methods Eight types of 0.025-inch guidewires were evaluated. The following structural properties were measured: tip length, tip deflection height, tip weight (TW), ratio of tip core weight to TW, shaft coating type (flat or uneven), outer diameter, and core wire diameter (CWD). Four performance tests were conducted to evaluate shaft stiffness as bending force (BF), shaft lubricity as friction force (FF), torque response as torque response rate (TRR), and seeking ability as total insertion success (TIS) in a technical test using a 3D bile duct model. The correlation coefficients of each variable were analyzed.Results The BF and CWDs were strongly correlated, as well as the FF and CWDs and BF. Among the guidewires with similar CWDs, the guidewires with uneven coating had significantly lower FF than those with flat coating. The TRR was strongly correlated with the CWDs; furthermore, guidewires with lower FF had better TRR. TIS was strongly correlated with the TRR, TWs, and ratio of the tip core weight to TW.Conclusions CWD affects shaft stiffness; CWD and coating type affect shaft lubricity and torque response. Because TRR and TW are correlated with seeking ability, an appropriate combination of core wire thickness, TW, and coating design is required to develop a guidewire with good seeking ability.
Keywords: Pancreatobiliary (ERCP/PTCD); Strictures; Endoscopic ultrasonography; Biliary tract; Interventional EUS